Parametrizing Epoch of Reionization foregrounds: A deep survey of low-frequency point-source spectra with the Murchison Widefield Array - Offringa, A.; Trott, C.; Hurley-Walker, N.; Johnston-Hollitt, M.; McKinley, B.; Barry, N.; Beardsley, A.; Bowman, J.; Briggs, F.; Carroll, P.; Dillon, J.; Ewall-Wice, A.; et al. (Oxford University Press, 2016)
© 2016 The Authors. Experiments that pursue detection of signals from the Epoch of Reionization (EoR) are relying on spectral smoothness of source spectra at low frequencies. This article empirically explores the effect of foreground spectra on EoR experiments by measuring high-resolution full-polarization spectra for the 586 brightest unresolved sources in one of the Murchison Widefield Array (MWA) EoR fields using 45 h of observation. A novel peeling scheme is used to subtract 2500 sources from the visibilities with ionospheric and beam corrections, resulting in the deepest, confusion-limited MWA image so far. The resulting spectra are found to be affected by instrumental effects, which limit the constraints that can be set on source-intrinsic spectral structure. The sensitivity and power-spectrum of the spectra are analysed, and it is found that the spectra of residuals are dominated by point spread function sidelobes from nearby undeconvolved sources. We release a catalogue describing the spectral parameters for each measured source.